A thermophilic β-mannanase from Neosartorya fischeri P1 with broad pH stability and significant hydrolysis ability of various mannan polymers. (15th April 2015) - Yang, Hong; Shi, Pengjun; Lu, Haiqiang; Wang, Huimin; Luo, Huiying; Huang, Huoqing; Yang, Peilong; Yao, Bin
Highlights: A novel GH 5 β-mannanase, Man5P1, was identified in thermophilic N. fischeri P1. Man5P1 was expressed in P. pastoris and showed optimal activity at pH 4.0 and 80 °C. rMan5P1 exhibited good stability over a broad pH range and at 60 °C and below. rMan5P1 had strong resistance to SDS and Ag + . rMan5P1 released linear/branched oligosaccharides of various lengths from mannans. Abstract: A new β-mannanase gene, man5P1, was cloned from the thermophilic fungus Neosartorya fischeri P1, and successfully expressed in Pichia pastoris . The predicted amino acid sequence of man5P1 consists of a putative 19-residue signal peptide at the N-terminus and a catalytic domain of glycoside hydrolase family 5. The purified recombinant Man5P1 (rMan5P1) was optimally active at pH 4.0 and 80 °C, and was acid and alkali tolerant, exhibiting >20% of the maximal activity at pH 2.0 and 9.0. rMan5P1 had better stability over a broad pH range of 2.0–12.0, and was highly thermostable at 60 °C and below. The enzyme was highly active towards galactomannan and glucomannan, and exhibited classic endo-activity producing a mixture of mannooligosaccharides (MOS). Moreover, it had strong resistance to SDS and Ag + and proteases. The superior properties make Man5P1 a potential candidate for use in various industrial applications.